Answer:
1/6
Step-by-step explanation:
I think this is tricky.
when you randomly choose the 1st two times, it doesn't matter as long as Na was not chosen, otherwise the probability would become ZERO for the 3rd one be Na.
So, after 1st two is removed, there are only 4 left in the pool, so picking Na at the 3rd draw is 1/4 probability.
But, come to think of it, when 1st draw, you have to draw the other 5 out of 6, 2nd draw the 4 out of 5, then 3rd is 1 Na out of the 4.
So, 5/6 x 4/5 x 1/4 = 1/6
i only know 10, sorry. but its 20.
hope this helps
Answer:
x = -6
Step-by-step explanation:
First write the equation.
4x + -3 = 5x + 3
The isolate x in the equation. Add -4x to both sides.
4x + -3 + -4x = 5x + 3 + -4x
-3 = x + 3
Then add -3 to both sides.
-3 + -3 = x + 3 + -3
-6 = x
Now you have the value of x = -6.
Cheers.
Hello from MrBillDoesMath!
Answer:
(1/3) x = (5/6)
Discussion:
I think you are asking for this equation:
(1/3) x = (5/6) => multiply both sides by 3
(1/3) 3 x = (5/6) 3 => as (1/3) *3 = 1
x = 5*3/6
x= 15/6
x = 5/2 = 2.5
Thank you,
MrB
Factor the following:
12 x^4 - 42 x^3 - 90 x^2
Factor 6 x^2 out of 12 x^4 - 42 x^3 - 90 x^2:
6 x^2 (2 x^2 - 7 x - 15)
Factor the quadratic 2 x^2 - 7 x - 15. The coefficient of x^2 is 2 and the constant term is -15. The product of 2 and -15 is -30. The factors of -30 which sum to -7 are 3 and -10. So 2 x^2 - 7 x - 15 = 2 x^2 - 10 x + 3 x - 15 = x (2 x + 3) - 5 (2 x + 3):
6 x^2 x (2 x + 3) - 5 (2 x + 3)
Factor 2 x + 3 from x (2 x + 3) - 5 (2 x + 3):
Answer: 6 x^2 (2 x + 3) (x - 5)